Statistical study of the ISM of GRB hosts. (5th March 2015) - de Ugarte Postigo, A.; Fynbo, J. P. U.; Thöne, C. C.; Christensen, L.; Gorosabel, J.; Sánchez-Ramírez, R.
Abstract: Gamma-ray burst (GRB) afterglows shine, during a brief period of time as the most luminous objects that can be detected in the Universe. They have been observed at almost any redshift, from our nearby environment (the nearest one, at z = 0.08) to the very distant Universe (the current record holder at z = 9.4). Their optical spectra are well reproduced by a clean, simple power law, making them ideal light houses to probe the interstellar medium of their host galaxies at any redshift. We have used the largest sample of GRB afterglow spectra collected to date to perform a statistical study of the interstellar medium in their host galaxies. By analysing the distribution of equivalent widths of the most prominent absorption features we evaluate the different types of environments that host GRBs and study their diversity.